Contribution to the diversity of the fossil record of turtles (Testudinata) from Chubut Province (Argentina) and its significance in understanding the evolution of turtles in southern South America - Sterli, Juliana (2021)
In this work we focus on the fossil record of turtles and tortoises from the Chubut Province, in Patagonia, Argentina. This record is the richest, most diverse, the longest and continuous in the country and one of the most important in the continent. In this work, we present and study new fossils from all known clades of turtles from the province, coming from targeted field campaigns, as well as from past investigations, placed in a comprehensive and detailed chronostratigraphic context. In Chubut, more than 241 occurrences of turtles from at least 223 collection points are known, spanning from the Toarcian (Jurassic) to the Tortonian (Miocene). we manage to fill some of the gaps in the fossil record, complete the anatomical knowledge of many taxa, explore new geographical areas, and present some important highlights. Among these, the record of the oldest pan-chelid turtles indicates the significant potential of the sedimentary deposits of Chubut. Furthermore, we discuss the changes in the diversity and faunal turnovers of the various turtle clades in this region during the last 180 Ma and across important events during the Cretaceous/Paleocene and Oligocene/Miocene boundaries.